Determination of Antibody Titration between Clinical and Community-Based Patients for O, H, AH and BH Antigens in Salmonella Samples - Wani, Nisar Ahmad; Kannaiyan, Jaianand; Paulraj, Balaji; Veeramani, Veeramanikandan (Journal of Drug Delivery and Therapeutics, 2019)
The aim of the study is to determine the baseline antibody titer of Salmonella bacteria in different positive samples with a view to establishing the significant titer for Widal agglutination test in Kashmir. The Widal test was performed on each serum. The slide agglutination test was first done and then positive samples were further subjected to tube agglutination for quantitative titration. The most commonly utilized diagnostic test for enteric fever is a Widal test, which detects agglutinating antibodies against the O, H, AH and BH antigens of S. typhi. The results of the Widal test showed that out of 413 samples 219 were positive for Antigen O, 165 were positive for Antigen H, 17 were positive for Antigen AH and 12 were positive for Antigen BH. The highest percentage cases were with Antigen-O whereas the lowest percentage was found in Antigen-BH. The difference between clinical and community-based patients have been studied. Keywords: Aetiology, Antigen, Enteric fever, Morbidity, Salmonella typhi, Widal test.